2020
DOI: 10.1371/journal.pone.0228321
|View full text |Cite
|
Sign up to set email alerts
|

Does prolonged television viewing affect Body Mass Index? A case of the Kingdom of Saudi Arabia

Abstract: Background The rising prevalence of overweight and obesity and their health implications is a major public health concern worldwide. This study set out to understand the relationship between the number of hours spent watching television and Body Mass Index (BMI) in the Kingdom of Saudi Arabia using data from the Saudi Health Interview Survey. Methods The study employed both ordinary least squares and quantile regressions to estimate the mean and distributional association of prolonged television watching and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…It has been remarked that NCD risk factors are extremely varied in their distribution across different socio-economic groups and their prevalence patterns rapidly change as societies develop ( 7 9 ). While some literature exists on the behavioral determinants of NCDs in the KSA ( 10 , 11 ), little is known about the corresponding socio-economic correlates of NCD risk factors. As a result, greater insight into the risk factor correlates is important in relation to forming policies and to provide an understanding of the factors that are expected to contribute to the Kingdom's NCD risk factors inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…It has been remarked that NCD risk factors are extremely varied in their distribution across different socio-economic groups and their prevalence patterns rapidly change as societies develop ( 7 9 ). While some literature exists on the behavioral determinants of NCDs in the KSA ( 10 , 11 ), little is known about the corresponding socio-economic correlates of NCD risk factors. As a result, greater insight into the risk factor correlates is important in relation to forming policies and to provide an understanding of the factors that are expected to contribute to the Kingdom's NCD risk factors inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that the prevalence of hypertension is increasing in the KSA, affecting 26.1 % of the adult population [7]. Other NCDs such as metabolic syndrome, diabetes mellitus, obesity, and dyslipidaemia are also on the rise in the KSA [8,9]. A recent study showed that increasing physical inactivity and maintenance of an unhealthy diet have led to an increase in the prevalence of these NCDs in the KSA [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the increased prevalence of non-communicable diseases, such as obesity, hypertension, hypercholesterolaemia, diabetes, asthma and cancer, with all the attendant risk factors, together with road traffic injuries, places significant burdens on the public healthcare of the KSA. [11][12][13][14][15][16][17] In the KSA, health expenditure per capita has increased in the last three decades, yet such expenditure is comparatively low when compared with other high-income countries of the world. For example, the percentage of gross domestic product dedicated to health in 2017 was 5.74, which is relatively low when compared to the average percentage reported for the high-income Organisation for Economic Co-operation and Development (OECD) countries.…”
Section: Introductionmentioning
confidence: 99%